The Study of Modified Trapa Bispinosa Roxb. Starch as a Natural Filler in Compact Face Powders - Prompamorn, Piyanuch; Itsarasook, Khwunjit; Chantree, Kanlayaporn; Komutiban, Orapin; Modesuwan, Surapa; Tanghiranrat, Jittarawadee; Chaivisuthangkura, Parin; Jindarat, Sarawut; Thophon, Suchada (Science Essence Journal, 2026)
This study aimed to prepare chemically modified starch from Trapa bispinosa Roxb. kernel for use as a filler in color cosmetic products to reduce the use of talcum in formulations due to concerns about potential contamination and safety issues. The starch was chemically modified using a 0.2 M sodium hydroxide solution, yielding 36.60 of modified starch that appeared as a fine, non-agglomerated powder free of foreign matter. Colorimetric analysis indicated a slightly yellowish-white appearance, with L*, a*, and b* values of 89.28±0.69, -1.71±0.04, and 7.19±0.06, respectively, and a whiteness index of 83.18±1.74. SEM analysis revealed oval starch granules with smooth surfaces, occasional small protrusions, and particle sizes ranging from 16.25 to 25.5 µm. The water and oil absorption capacities were 0.40±0.15 and 0.35±0.20 mL/g, respectively. Cytotoxicity evaluation using human dermal fibroblast cells demonstrated no cellular toxicity, indicating biocompatibility and suitability for cosmetic applications. Flowability assessment based on the angle of repose, Carr’s index, and Hausner ratio indicated good flow properties. Compact face powder formulations containing modified T. bispinosa Roxb. starch at concentrations ranging from 12.5% to 50% were developed, and the results showed that the modified starch could replace talcum at levels up to 25% without adversely affecting the physical properties of the formulation.